Conchostracans and insects from the Upper Triassic of the Biobío river (“Santa Juana Formation”) from Chile - Gallego, Oscar Florencio; Martins-Neto, Rafael G.; Nielsen, Sven Nikolaus
Fossil arthropods from Upper Triassic outcrops along the Biobío river, south-central Chile, are reported in this paper. Two species of the order Coleoptera, Ademosyne sp., and Ischichucasyne santajuanaensis gen. et sp. nov. (Permosynidae) are described for the first time for the Triassic of Chile. The conchostracans Menucoestheria terneraensis Gallego and Polygrapta troncosoi (Gallego) comb. nov., are re-examined based on newly collected specimens and scanning electron microscope photographs. A close relation between M. terneraensis and Argentinean and Antarctic species is postulated, with the possibility that Menucoestheria evolved from Euestheria Depéret y Mazerán. Menucoestheria could be the origin of all other Gondwanic eosestherids. The use of Menucoestheria and Polygrapta as fossil guides for continental levels of the Upper Triassic of Argentina and Chile is tentatively proposed. The reported entomofauna, which exhibits close affinities with the Argentinean entomofauna, sharing, for example, the genera Ademosyne and Ischichucasyne, broadens our knowledge of South American arthropod diversity during the Triassic. The presence of the homopteran dysmorphoptilid Bandelnielsenia Martins-Neto and Gallego, the most plesiomorphic of the South American forms, seems fundamental for an understanding of the phylogeny of this important Triassic group En este trabajo se da a conocer el hallazgo de artrópodos del Triásico Superior, en estratos que afloran a lo largo del río Biobío, en el centro sur de Chile. Se describen, por primera vez, para el Triásico de Chile, representantes del orden Coleoptera: Ischichucasyne santajuanaensis gen. et sp. nov. y Ademosyne sp. (Permosynidae). Sobre la base de nuevos materiales recolectados y fotografías de detalle con microscopía electrónica de barrido, se reestudiaron los conchóstracos Menucoestheria terneraensis Gallego y Polygrapta troncosoi (Gallego) comb. nov. Se destaca la estrecha relación entre M. terneraensis Gallego y otras especies de Argentina y Antártica. Se menciona ...